Integrated analyses of Mendelian randomization, eQTL, and single-cell transcriptome identify CCN3 as a potential biomarker in aortic dissection - Haoyu Ran; Changying Li; Syed M. Musa Rizvi; Ruiqin Zhou; Lingwen Kong; Sun Shuangling; Yue Shao; Kejia Wu; Changzhu Duan; Jun Luo; Haoming Shi; Qingchen Wu; et al. (Scientific Reports)
Abstract Plasma secretory proteins are associated with various diseases, including aortic dissection (AD). However, current research on the correlation between AD and plasma protein levels is scarce or lacks specificity. This study aimed to explore plasma secretory proteins as potential biomarkers for AD. Through genome-wide association studies, expression quantitative trait locus (eQTL) analysis, and human plasma protein profiling, we identified DBNL, NPC2, SUMF2, and TFPI as high-risk genes and CCN3, PRKCSH, TEX264, and TGFBR3 as low-risk genes for AD. Further cell localization and differential expression analysis of these eight genes were conducted using single-cell data. We also examined their expression in three Gene Expression Omnibus datasets, measured their mRNA levels in AD versus normal tissues using qPCR, and assessed their protein levels in patients’ blood versus healthy individuals using enzyme-linked immunosorbent assay. Our findings suggest that CCN3, consistently downregulated in both mRNA and plasma levels during AD, may have a protective role. Initial enrichment analyses of differentially expressed CCN3 cells suggested their involvement in focal adhesion, actin cytoskeleton regulation, and the PI3K-Akt signaling pathway.